1996
DOI: 10.1051/jp2:1996156
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Polyelectrolyte Solutions on Surfaces: A Debye-Hückel Theory

Abstract: The adsorption onto a solid surface of a flexible polyelectrolyte solution in equilibrium with a reservoir is investigated. Both the electrostatic and the short-ranged interactions with the interface are taken into account. The polyelectrolyte chains are supposed to be infinitely long and to obey Gaussian statistics. We obtain analytical results for the concentration profiles within the framework of a mean-field theory and in the limit of weak adsorption (linear approximation). At high salt concentration, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(129 citation statements)
references
References 0 publications
3
125
1
Order By: Relevance
“…Density oscillations are still observed, although the amplitude is very small. Larger oscillations have been observed in polyelectrolyte solutions, [25][26][27] but these oscillations have a different origin. It was shown that the oscillations in polyelectrolyte solutions cannot be attributed to the ordering of individual coils, but that they are due to a balance between the segment-segment electrostatic interactions and the translation entropy of the chains.…”
Section: Resultsmentioning
confidence: 99%
“…Density oscillations are still observed, although the amplitude is very small. Larger oscillations have been observed in polyelectrolyte solutions, [25][26][27] but these oscillations have a different origin. It was shown that the oscillations in polyelectrolyte solutions cannot be attributed to the ordering of individual coils, but that they are due to a balance between the segment-segment electrostatic interactions and the translation entropy of the chains.…”
Section: Resultsmentioning
confidence: 99%
“…Attractive interactions were also obtained by Podgornik [27] for the case of fixed adsorbed amount and without considering the nonlinear excluded volume interaction. For polyelectrolytes in a poor solvent, Châtellier and Joanny [28] have obtained oscillations in the polymer concentration as well as in the inter-surface interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The Debye-Hückel theory has also been applied to polyelectrolyte adsorption on surfaces by Ch atellier and Joanny 24) . In order to demonstrate the effect of the ions on the interactions, we need to obtain DF in terms of the molecular densities.…”
Section: A2mentioning
confidence: 99%